Prinsip Kehadiran Terdakwa pada Persidangan Pidana Elektronik di Masa Pandemi Covid-19: Perbandingan Indonesia dan Belanda - Edwin Ligasetiawan; Febby Mutiara Nelson (Fakultas Hukum Universitas Jambi, 2022)
The COVID-19 pandemic has caused changes to the criminal justice system in many countries in the world, one of which is the trial methods using electronic devices such as videoconferencing. This change has an impact on the fulfillment of the defendant’s right of presence before the court as regulated in the Indonesia Criminal Procedure Code. The presence of the defendant is one of the basic rights in a trial, which also ensures the implementation of a fair trial because it is related to the evidentiary process. In this article, the principle of the defendant’s presence in electronic criminal trials is discussed by comparing Indonesian and Dutch laws. This study demonstrates that electronic criminal trials in Indonesia are only regulated in a Supreme Court Regulation and they are in conflict with the Indonesia Criminal Procedure Code; whereas in the Netherlands, despite its regulation in the Dutch Criminal Procedure Code, the use of videoconferencing is considered a violation of the provisions of the European Convention on Human Rights. This article argues that an electronic criminal trial requires the defendant’s agreement or provision that guarantees the rights of the defendant, because this trial overrides the defendant’s right of presence before the court. Abstrak Pandemi covid-19 turut memengaruhi perubahan sistem peradilan pidana pada berbagai negara di dunia, salah satunya adalah metode persidangan bersaranakan alat elektronik seperti videoconference. Perubahan ini berdampak pada hak terdakwa untuk hadir di muka pengadilan, yang di Indonesia diatur dalam KUHAP. Kehadiran terdakwa ini merupakan salah satu hak dasar terdakwa dalam suatu persidangan, yang turut menjamin pelaksanaan peradilan yang adil (fair trial) karena berkaitan dengan proses pembuktian. Dalam artikel ini prinsip kehadiran terdakwa dalam persidangan pidana elektronik dibahas melalui perbandingan hukum Indonesia dan Belanda. Hasil kajian menunjukkan, sidang pidana elektronik di Indonesia hanya diatur dalam Peraturan Mahkamah Agung dan ini berbenturan dengan KUHAP; sedangkan di Belanda, sekalipun telah dituangkan dalam KUHAP, penggunaan videoconference dianggap melanggar ketentuan European Convention on Human Rights. Artikel ini berpendapat, persidangan pidana secara elektronik memerlukan persetujuan terdakwa atau ketentuan yang menjamin seluruh hak-hak terdakwa dapat dipenuhi, sebab persidangan demikian itu mengenyampingkan hak terdakwa untuk hadir di muka sidang.